The World at War HD (1080p) - Ep. 13 - Tough Old Gut: Italy (November 1942 – June 1944) - Hangabur (NC, 2026)
Vidéo YouTube proposée par Hangabur. Emphasizes the difficult Italian Campaign beginning with Operation Torch in North Africa, the invasion of Sicily; Salerno,.
Droits : Vidéo publique YouTube. Droits conservés par le diffuseur.
Keywords: vidéo; youtube; patrimoine; culture; documentaire; Patrimoine